The Study of Kinetic Colloidal Particles in Magnetic Fluids using Diffraction Effect on an Optical Grating Created by Intersecting Laser Beams - Stelina, Julius; Musil, Ctibor (Communications - Scientific letters of the University of Zilina, 2003)
In this paper a short characteristic of magnetic fluids and some of their applications are presented a simple one-dimensional model of creation of thermal and absorption grating is explained. The method of generation of optical grating by using the interference two intersecting coherent laser beams is presented. In conclusion some possibilities of utilisation optical created grating are also indicated.